PENGEMBANGAN PEREKONOMIAN BURUH PABRIK TERDAMPAK PANDEMI COVID-19 - Yulfan Arif Nurohman; Rina Sari Qurniawati (ABDI MAKARTI, 2022)
The implementation of community service activities aims to provide solutions to the problems that factory workers have been affected by COVID-19. As a result of the prolonged Covid-19 pandemic, the company suffered losses and made a policy that most factory workers in Salatiga City and Semarang Regency experienced layoffs and were laid off by the company. The method used in community service activities is to provide training to factory workers who have been affected by the COVID-19 pandemic and have been laid off and sent home. Activities in the implementation of community service include activities to identify and explore community potential, create SMEs centers and joint business groups, guidance on access to capital and business management, and training on the use of information technology as marketing development. The results of community service activities, participants have an understanding of the management and development of highly competitive SMEs through the use of information technology